Growth and condition factor of rivulated parrotfish, Scarus rivulatus in Kulisusu Bay, North Buton, Southeast Sulawesi - Gusrin, Gusrin; Asriyana, Asriyana; Bahtiar, Bahtiar (JSIPi (Jurnal Sains dan Inovasi Perikanan) (Journal of Fishery Science and Innovation), 2020)
The growth and condition factor of rivulated parrotfish (Scarus rivulatus) was studied in Kulisusu Bay of  North Buton Southeast Sulawesi from April to July 2019.  Fish samples were collected using gillnets of 11/2, 2, and 21/2 inches mesh size. Growth parameters were analyzed following von Bertalanffy formula using ELEFAN I software of package program of FiSAT II. A total of 300 fish individuals was caught  ranging from 145-300 mm in the total length and 63.8-461.8g in weight. The length–weight relationship of male was isometric, while female and combined sexes were negative allometric. The von Bertalanffy growth models for male, female, and combined sexes, were Lt = 310.8{1- e -0.89(t-0.011)}; Lt = 230.48{1- e -0,46(t+0,16)};  Lt = 304.5{1- e -1,2(t-0,064)}, respectively. A high value of b in male indicates this fish is getting enough food. The relative condition factor of fish varied from 0.80 to 3.45. The male has greather condition factors than female fish during this research. This shows male fish in good condition.